Development and Evaluation of Combined Effect Buccal Films for Treatment of Oral Candidiasis - DURMUŞOĞLU, LÜTFİYE (My University, 2023)
© 2022, The Author(s), under exclusive licence to American Association of Pharmaceutical Scientists.Buccal film formulations, including antifungal nystatin, anti-inflammatory agent hydrocortisone acetate, and local anesthetic lidocaine hydrochloride for pain relief, were developed. Bioadhesive films were fabricated with hydrophilic polymers, hydroxyethyl cellulose (HEC), and xanthan gum (XG) and dried in the incubator. Textural, swelling, and bioadhesive properties, physicochemical and in vitro release characteristics, and antifungal activities of bioadhesive films were evaluated. Bioadhesive films significantly extended nystatin release by prolonging retention time of the target area formulation while rapidly releasing hydrocortisone acetate and lidocaine HCl, reducing drug administration. The polymer type affected bioadhesion strength and erosion ratio, and XG formulations had more polymer suitability. Consequently, XT-O2 formulation that was prepared with xanthan gum and tween 80, was best for its highest antifungal film activity (20.00 ± 0.07 mm), released nystatin (44.296% ± 1.695), and lowest erosion matrix (36.719% ± 0.249). The selected formulation can be used for compatibility, stability and in vivo studies targeted oral candidiasis infections. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TROPİKAL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; TROPICAL MEDICINE; Farmasötik bilim; Yaşam Bilimleri; Pharmaceutical Science; Life Sciences; buccal drug delivery; hydrocortisone acetate; lidocaine hydrochloride; mucoadhesive film; nystatin; oral candidiasis; xanthan gum